Determining Factors for the Development of Critical Thinking in Higher Education - Dora Lucia Jaramillo Gómez; Annie Julieth Álvarez Maestre; Abad Ernesto Parada Trujillo; Carlos Alfredo Pérez Fuentes; Dago Hernando Bedoya Ortiz; Ruth Katherine Sanabria Alarcón (Journal of Intelligence, 2025)
This study arises from the growing need to train professionals capable of confronting and analyzing the overabundance of information in an increasingly complex world, where critical thinking is seen as an indispensable skill for informed decision making and problem solving. To this end, a systematic narrative review methodology was applied to the scientific literature, compiling data from various international databases. The results reveal that physiological factors (memory, attention, nutrition and physical activity), psychological factors (cognitive biases, fear of ambiguity, and metacognition), sociocultural factors (diversity, inequality, and cultural norms), technological factors (digitalization, use of AI, and digital literacy), and educational factors (active pedagogical strategies and collaborative work) play a determining role in the development of critical thinking in higher education. The discussion emphasizes the complex interaction between these factors and underscores the need for holistic approaches that strengthen both cognitive competencies and emotional well-being. In conclusion, we recommend designing comprehensive training interventions that consider the identified factors, promoting inclusive and reflective environments, aimed at developing critical, autonomous graduates capable of facing contemporary challenges.